PENGARUH KNOWLEDGE SPILLOVERS TERHADAP PERTUMBUHAN INDUSTRI DI KAWASAN INDUSTRI JAWA TENGAH - Pujiati, Amin (Universitas Negeri Semarang, 2009)
This research aims to analyze the influence of the knowledge spillovers on the industry growth inCentral Java. It uses district-level data on two digit International Standard Industrial Classification of AllEconomic Activities (ISIC) and supplied by the Indonesian Central Bureau of Statistics in 2001 and 2006.The tools of the analysis used multiple regression model with Ordinary Least Square (OLS) method.The regression result shows that Specialization negatively influences of the industry growth. Theresult of this finding shows the opposite sign of Dynamic Externalities Marshall-Arrow-Romer (MAR) andPorter theory .Diversity and competition have positive impact on the industry growth. This is apprppriateand support the Porter theory and deny the MAR theory which stated that the local monopoly willincrease the industry growth . The diversity of the result in district is positive. This result matches andconsisant with Jacobs theory of the industry diversity.Keywords: knowledge spillovers, dynamic externalities , industry growth.